Cross-sectional survey to explore knowledge, attitude, practices and impact of an intervention programme related to antibiotic misuse and self-medication among general population of Pakistan - Tahir Mehmood Khan; Arifa Saif; Allah Bukhsh; Muhammad Osama Yaseen; Alia Saif (BMJ Public Health)
Objective The objective of this study is to observe the knowledge, attitude and practices related to antibiotic use, the prevalence of self-medication and non-adherence to the prescribed course of antibiotics across Pakistan.Method A cross-sectional quantitative study on knowledge, practices, attitude and adherence to antibiotic therapy was conducted from January 2021 to March 2022 among the adult population living in different areas across Pakistan. Individuals with poor knowledge were selected for video-based intervention programme. Video template produced by WHO to create antibiotic awareness was used for this purpose. A postintervention study was conducted to assess the improvement in their knowledge and practices regarding the use of antibiotics. Paired samples t-test was applied to assess the improvement in postintervention survey scores.Results 68.9% (n=340/493) of the participants were female and the majority of the sample population was from urban areas. Our study revealed that 39.2% (n=196) of individuals have undergone self-medication with antibiotics in the last 6 months and 42% (n=207) of the total participants were non-adherent to antibiotic treatment plan. Lack of proper information from healthcare professionals was observed to be the most important barrier to antibiotic treatment adherence. The interventional video was shown to 31.64% (n=156/493) of participants who lack proper knowledge about antibiotic use and its associated problems. There appeared to be a significant improvement in the postintervention mean scores of knowledge, practices, attitude and adherence related to antibiotics.Conclusion This study highlights the alarming situation of self-medication and non-adherence to antibiotic therapy. To cope with the situation, certain pertinent measures are direly needed before the precious lifesaving antibiotics become useless in eradicating various controllable microbial diseases.